2009
DOI: 10.1152/ajpcell.00634.2008
|View full text |Cite
|
Sign up to set email alerts
|

Role of γ-glutamyl transpeptidase in redox regulation of K+ channel remodeling in postmyocardial infarction rat hearts

Abstract: -␥-Glutamyl transpeptidase (␥-GT) is a key enzyme in GSH metabolism that regulates intracellular GSH levels in response to extracellular GSH (GSHo). The objective of this study was to identify the role of ␥-GT in reversing pathogenic K ϩ channel remodeling in the diseased heart. Chronic ventricular dysfunction was induced in rats by myocardial infarction (MI), and studies were done after 6 -8 wk. Biochemical assays of tissue extracts from post-MI hearts revealed significant increases in ␥-GT activity in left v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
0
11
1
Order By: Relevance
“…Based on fi ndings in rats that GGT interacts with redox regulation of potassium channels in the postmyocardial infarction heart, we speculated that elevated GGT may predispose to ventricular tachyarrhythmia [16]. Our study, however, does not support this notion, as appropriate ICD therapy did not correlate with GGT levels.…”
Section: Discussioncontrasting
confidence: 73%
“…Based on fi ndings in rats that GGT interacts with redox regulation of potassium channels in the postmyocardial infarction heart, we speculated that elevated GGT may predispose to ventricular tachyarrhythmia [16]. Our study, however, does not support this notion, as appropriate ICD therapy did not correlate with GGT levels.…”
Section: Discussioncontrasting
confidence: 73%
“…6), and thus the precise relationship between the Trx system and Kv4 channel expression is unclear. We reported previously that short-term (4-6 h) treatment of isolated ventricular myocytes from sham hearts with AF did not significantly decrease I to density (46), but in another study we showed that normal rats treated for 3 days with buthionine sulfoximine (a blocker of GSH synthesis) plus 1,3-bis-(2-chloroethyl)-1-nitrosourea (an inhibitor of TrxR and glutathione reductase) had marked decreases in Kv4 channel mRNA, protein abundance, and I to density in the LV (21). In agreement with the present study, downregulation of I to density with oxidoreductase inhibition was also reversed in vitro by stimulation of receptor tyrosine kinase signaling with the insulin-mimetic, bpV(phen) (21).…”
Section: Igf-1 Effects In Sham Heartsmentioning
confidence: 83%
“…In previous studies, we also documented the pathogenic condition of oxidative stress in this MI model. In particular, there is marked impairment of the thioredoxin and glutaredoxin systems in the surviving regions of the left ventricle (24,31,32), and isolated myocytes from post-MI hearts are characterized by significantly increased ROS levels and lower concentrations of reduced glutathione (GSH) (23,42).…”
Section: Resultsmentioning
confidence: 99%